Projeto estrutural de pavimentos de aeroportos regionais: uma aplicação do procedimento da Federal Aviation Admnistration (FAA) para o cenário brasileiro - Caldana, Pedro Henrique Del Agnolo (Universidade Federal de São Carlos, 2023)
The design of airport pavements, whether rigid or flexible, involves calculations based on various variables such as aircraft weight, traffic intensity and frequency, design lifespan, and others. Currently, in Brazil, it is common to use foreign methodologies for the development of airport pavement infrastructure. This work consists of an adaptation of the Federal Aviation Administration (FAA) guidelines to the Brazilian context by determining design variables suitable for national airports. Using the FAARFIELD (Federal Aviation Administration Rigid and Flexible Iterative Elastic Layered Design) version 2.0, developed by the American agency, pavements of both flexible and rigid types were dimensioned with various characteristics and specifications. Subsequently, these pavements were analyzed and compared to assess the influence of these variables on structural performance. Through simulations, it was possible to better understand the influence of design conditions and pavement material characteristics on layer thickness calculations, especially the subgrade's modulus of elasticity. At the end of the design process, the calculated structures had their strengths assessed using the ACR/PCR (Aircraft Classification Rating/Pavement Classification Rating) method, performed by FAARFIELD 2.0. Subsequently, the design results were compared based on a cost estimate, generated from priced compositions in the new database provided by Infraero, the SINAPI (National System of Costs and Civil Construction Indexes). In conclusion, it was found that the method employed has limitations related to Brazilian practices, but these can be overcome through adaptations allowed by the software itself. Finally, it was possible to obtain results that met the project's conditions satisfactorily, a process that can be employed for future airport construction projects in Brazil.
Structural design of regional airport pavements: an application of the Federal Aviation Administration (FAA) procedure for Brazil
Keywords: Pavimento aeroportuário; Aeroportos regionais; FAARFIELD; Pavimento rígido de concreto; Pavimento flexível; Projeto; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES